The Shank3 Interaction Partner ProSAPiP1 Regulates Postsynaptic SPAR Levels and the Maturation of Dendritic Spines in Hippocampal Neurons - Reim, Dominik; Weis, Tobias M.; Halbedl, Sonja; Delling, Jan Philipp; Grabrucker, Andreas M.; Boeckers, Tobias M.; Schmeisser, Michael J. (Frontiers in Synaptic Neuroscience, 2016)
The postsynaptic density or PSD is a submembranous compartment containing a wide array of proteins that contribute to both morphology and function of excitatory glutamatergic synapses. In this study, we have analyzed functional aspects of the Fezzin ProSAPiP1, an interaction partner of the well-known PSD proteins Shank3 and SPAR. Using lentiviral-mediated overexpression and knockdown of ProSAPiP1, we found that this protein is dispensable for the formation of both pre- and postsynaptic specializations per se. We further show that ProSAPiP1 regulates SPAR levels at the PSD and the maturation of dendritic spines. In line with previous findings on the ProSAPiP1 homologue PSD-Zip70, we conclude that Fezzins essentially contribute to the maturation of excitatory spine synapses.